Comparative Analysis of Maize Physico-Chemical Parameters and Mycotoxin Levels in Dual Environments - Carbas, Bruna (2024)
Funding Information: This research was funded by the National Funds by Rural Development Program through the operational group QUALIMILHO\u2014new sustainable integration strategies that guarantee quality and safety in the national maize, PDR2020 n\u00BA 101-031295 (2017\u20132020). This work was also supported by FCT, the Portuguese Foundation for Science and Technology, through the R&D unit, to GREEN-IT, Bioresources for Sustainability (UIDB/04551/2020), and CIMO (UIDB/00690/2020 and UIDP/00690/2020). This research was also funded by PT national funds (FCT/MCTES, Funda\u00E7\u00E3o para a Ci\u00EAncia e Tecnologia and Minist\u00E9rio da Ci\u00EAncia, Tecnologia e Ensino Superior) through the grant UIDB/00211/2020. Publisher Copyright: © 2024 by the authors.